Characterization of Cotton Fiber Filled Polyvinyl Alcohol Films - Low, Chong Yu; Lim, Soo King; Ng, Yee-Kuang; Yong, Tzyy Jeng (Journal of Engineering and Technology (JET), 2022)
Petroleum based polymer films have high resistance toward degradation and bring about countless environmental problems where there are a lot of obstacles and restraint causes inadequacy of recycling, contributing to accumulation of terrific waste. To counter the low degradability of plastic waste, it can be conquered with the development of biopolymer by adding organic fibers, which makes the films to be more biodegradable. In this study, cotton fiber filled polyvinyl alcohol (PVA) films were prepared with various cotton fibers loading, which are 0, 5, 10, 15 and 20 wt. % in 20g, 25g and 30g of PVA. Fourier transform infrared spectroscopy analysis discovered that both cotton fiber and PVA were hydrophilic in nature and confirmed that there was no chemical interaction formed between cotton filler and PVA matrix. This study is aimed to highlight on the tensile properties, hardness and thermal stability of the PVA/Cotton fiber blended films. Moreover, the investigation on the surface morphology and surface fracture of the blended films were conducted by using scanning electron microscopy. Based on the result obtained, PVA/ Cotton blended films with higher cotton fiber loading demonstrated lower tensile strength and elongation at break due to the weak intermolecular bonding between the cotton fiber and the PVA matrix. However, the tensile modulus was improved gradually as the increment of cotton fiber loading those results in stiffer blended films as compared to pure PVA film. Hardness value of the PVA/Cotton fiber shows a significant boost when cotton fiber is added as filler into the PVA matrix as well. Besides, thermal stability of the blended films also shows a minute improvement as the cotton fiber loading increases.